Respuesta :
Answer:
Yes, z will be greater than x.
Step-by-step explanation:
Given expression is [tex]x- (-y)=z \ for \ y \ is \ a \ positive \ integer.[/tex]
now let y = 2 and x = 1
Then, [tex]x- (-y)=z \\1+2 = 3 \\\\[/tex]
where [tex]z> x[/tex] i.e. 3 > 1
on simplifying the given expression in terms of y
[tex]y=z-x[/tex]
now suppose if x = 7 and z=3 then,
[tex]y = (z-x) = (3-7) = (-4)[/tex]
which gives value of y in terms of negative integer which is not possible according to the given statement since y is a positive integer. Therefore, if y is a positive integer then z will be greater than x.
Integers are all numbers without decimal point.
z will always be greater than x
Given that:
[tex]x - (-y)=z[/tex]
Open the bracket
[tex]x + y=z[/tex]
Rewrite as:
[tex]z =x + y[/tex]
From the question, we understand that y is positive.
This means that, irrespective of whether x is positive or negative; the value of z will always be greater than x.
Read more about integers at:
https://brainly.com/question/1768254